Phase extraction from electronic speckle patterns by statistical analysis - Tay, Cho Jui (2011)
In electronic speckle pattern interferometry (ESPI), speckles are information carriers as well as noise that hinders the extraction of high quality phase. This paper presents a phase extraction method based on the statistical property of speckles. Assuming that speckle related phase is a random variable having a uniform distribution, the grey level variance of a number of pixels is found to be related to the modulation intensity of a speckle pattern. The relation is used to establish a connection between the phase to be measured and the variance of grey level difference between two speckle patterns. Subsequently, a phase map wrapped in [0,π) is extracted. In order to obtain a standard 2π wrapped phase map, an initial one step phase shift is introduced. The phase value of a pixel under consideration is obtained from the grey levels of its N×N neighbouring pixels. The optimal value of N is obtained based on a qualitative analysis of the initial results. With an appropriate value of N, an accuracy of 1% can be achieved.